The medicinally important leafy vegetables of south western Nigeria (2005)
This paper focuses on twenty eight medicinally important leafy vegetables documented from the South western part of Nigeria. It also highlights their medicinal importance in the treatment of minor ailments as well as their sources. The family Compositae (Asteraceae) contained the highest number of plants followed by the Cucurbitaceae, Malvaceae and Solanaceae. Sixty eight percent of the documented vegetables are cultivated, eleven percent is usually obtained in the wild while twenty one percent is either cultivated or obtained from the wild. The need for concern on the conservation of genetic resources of these plants (especially those in the wild) is stressed in order to safeguard them for future generations and avoid their genetic erosion. The establishment of a gene/seed bank for vegetables is advocated.